EVALUASI AKURASI PERHITUNGAN HARGA POKOK PRODUKSI PADA PRODUK OLAHAN KELOR UMKM MATANARI - Jannah, Raodhatul; Zuhroh, Siti; Widyatama, Arif (Bisnis-Net, 2025)
This study was conducted in UMKM Matanari Sibedi Village In Sigi Marawola District. To see how this study aims to alternative strategy the determination of the cost of goods manufactured that can be used by UMKM Matanari to support an increase in income and how  UMKM comparing the income level if using the cost of goods manufactured by alternative calculation and preliminary model. The method of analysis of the data used is descriptive by adopting a case study.The result of this study the alternative calculation joint cost can hel increase the income in excess of this method can allocate the imposition of the cost of all costs is properly used, the reckoning also visible differences and the impostion of a fee so that the costs of goods production early model having lower than in the alternative calculation.